Leadership In The Public Library : Case Study In Tenteram City Public Library - Al Fatih, Muhammad Irsyad; Wijayanti, Luki (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
In the formal and informal organization, it is always found someone who is considered more prominent than others, who then appointed or designated as a leader. The Leader of an organization is expected to have leadership qualities, which showed his skills in leading organizations. A leader in the library requires synergy between skills in library management and leadership in general in order to create a good working atmosphere and to encourage the library staff in providing the best services to the patron community. Tenteram City Public library since year of 2018 has never experienced a change of its leader. Research using qualitative approach aimed to identify the leadership of Tenteram City public library leader in developing human resources and library services. Data of this study is gathered through observation and interviews. It is found that the head of the library serves as a role model in imbedding working discipline, he never involved the staff in decision making, the fear of making mistake is the working atmosphere created in the library. The Research found that the head of Tenteram City public library adopts autocratic leadership.